Looping into hyperspace: Mechanisms of distributed imagination during a collaborative multimodal science fiction writing project. (June 2021) - Kolovou, Maria; Shen, Ji; Smith, Blaine E.
Highlights: Imagination is distributed in different and dynamic ways between collaborators. Distributed imagination occurs in the duality of real and imaginary world. Collaborative imagination flows towards a shared space. Emotions can act as a bridge between the real and the imaginary world. Abstract: Imagination is critically important in student learning and development. However, it does not receive enough attention in mainstream schooling. In cases when imagination is forefronted, it has often been interpreted as capacity within individual minds. We created an integrated STEM learning program that aims to help students develop imaginative capacity while they work in small teams to produce multimodal science fictions. Adopting a framework based on imagination loop (Zittoun & Gillespie, 2015) and distributed cognition (Cole & Engeström, 1993 ), we examined how a pair of sixth grade students engaged in distributed imagination. Through conversation and interaction analysis, we illustrated how imagination is distributed in different ways between the pair. Findings point to the phases and features of imaginative loops that result in collaborative production. Our analysis demonstrates the value of documenting the detailed shifts in participants' perceptions of their tasks, products, partners, and relationships with each other over the course of their collaborations.